The Development of Syari'ah Cooperatives Information System Model - Ronny Malavia Mardani; Budi Wahono (University of Islam Malang, 2017)
Indonesian Muslims have tremendous potential to be a pioneer and world Islamic economic center. Indonesia is the country with the largest Muslim population in the world. Indonesia has made policies that encourage the development of the Islamic finance industry. Classic problems that hinder in the development of Cooperative Shari'ah is limited knowledge of the cooperative management in financial management. Recognizing these circumstances, it would require a new technological innovation that the managers of cooperatives Syariah that some of those who do not understand how to manage the financial well be understood and easy to apply. Therefore, it is necessary to design the automated information system with the technology, so that businesses in the Cooperative Syariah able to easily prepare their own financial statements, without having to understand the concept of financial management. The purpose of this study is the description and design accountable models of Shari'ah cooperative information systems. The method used in this study is a qualitative method that is by arranging the Prototype Model. Results of design research model of this system, is able to develop a model of cooperative systems that facilitate cooperative Shari'ah management preparing financial reports quickly and accurately, can help managers and members of cooperatives Shari'ah to determine the growth cooperatives quickly and can help managers to make decisions rapidly.Keywords: Cooperative Shari'ah, Management Information SystemsJudul Asli : Pengembangan Model Sistem Informasi Koperasi Syariah Berbasis Teknologi Informasi